Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/1873-3468.13344
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants on extracellular loop domains that dictate interaction between β‐arrestin and human APJ receptor

Abstract: The human APJ receptor (APJR), activated by apelin isoforms, regulates cardiovascular functions and fluid homeostasis. Understanding its structure‐function relationship is crucial for a comprehensive knowledge of signalling aberrations that cause several physiological disorders. Here, we demonstrate the influence of extracellular loop (ECL) domains in the mechanism of β‐arrestin‐mediated signalling from human APJR: Apelin system. Alanine mutations of evolutionarily conserved residues were characterized using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Receptor internalization assay was done as per our previous report [24]. HEK293T cells, transiently transfected with APJR and its ECL mutant plasmids, were treated with 10 µ m apelin‐13 peptide and incubated further at 37 °C with 5% CO 2 for 1 h. The cells were then fixed on glass slides and receptor internalization was imaged using confocal microscope (Leica DMi8; Leica Microsystems, Wetzlar, Germany), by monitoring the fluorescence signal from eGFP tag.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Receptor internalization assay was done as per our previous report [24]. HEK293T cells, transiently transfected with APJR and its ECL mutant plasmids, were treated with 10 µ m apelin‐13 peptide and incubated further at 37 °C with 5% CO 2 for 1 h. The cells were then fixed on glass slides and receptor internalization was imaged using confocal microscope (Leica DMi8; Leica Microsystems, Wetzlar, Germany), by monitoring the fluorescence signal from eGFP tag.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we have identified 'hot spots' in ECL2 (T 169 , T 170 , Y 182 , T 190 , W 197 ) and ECL3 (L 276 , L 277 , W 279 ) of human APJR that control receptor activation by the coordinated movement of extracellular domains, which later transmit to the intracellular domains for effector coupling. Our earlier studies revealed that motifs 183 MDYS 186 and 268 KTL 270 in ECL2 and ECL3 are imperative for biased signaling of apelin receptor [23,24]. In general, hydrophobic residues of ECL2 are presented as important structural motifs that 'lock' the ligand in its binding pocket, and thereby enhance ligand residence time for GPCR interaction [75].…”
Section: Receptor Mutantsmentioning
confidence: 99%
See 3 more Smart Citations